Пошаговое объяснение:
-6,3x(-3y)=18,9ху
8a-2c-13a+c= - 5а-с
m-(18+m)+(12-m)=m-18-m+12-m= -m-6
-5(-4+y)+8(y+3) = -20-5y+8y+24=3y+4
1.
2.
3.
4.
Пошаговое объяснение:
-6,3x(-3y)=18,9ху
8a-2c-13a+c= - 5а-с
m-(18+m)+(12-m)=m-18-m+12-m= -m-6
-5(-4+y)+8(y+3) = -20-5y+8y+24=3y+4
1.![-6,3x*(-3y)=18,9xy](/tpl/images/1217/5253/ba1a4.png)
2.![8a-2c-13a+c=-5a-c](/tpl/images/1217/5253/b82f1.png)
3.![m-18-m+12-m=-6-m](/tpl/images/1217/5253/a2fe6.png)
4.![-5(-4+y)+8(y+3)=20-5y+8y+24=3y+44](/tpl/images/1217/5253/370c7.png)